2018
DOI: 10.1103/physrevmaterials.2.074802
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh critical current densities, the vortex phase diagram, and the effect of granularity of the stoichiometric high- Tc superconductor CaKFe4As4

Abstract: We present a comprehensive study of the critical current densities and the superconducting vortex phase diagram in the stoichiometric superconductor CaKFe4As4 which has a critical temperature of ∼ 35 K. We performed detailed magnetization measurements both of high quality single crystals for different orientations in an applied magnetic field up to 16 T and for a powder sample. We find an extremely large critical current density, Jc, up to 10 8 A/cm 2 for single crystals when H||(ab) at 5 K, which remains robu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
69
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 63 publications
(104 reference statements)
20
69
5
1
Order By: Relevance
“…This supports the extremely large critical current densities, reported previously for CaKFe 4 As 4 in Ref. [14]. The small coherence length of CaKFe 4 As 4 is compatible with the presence of the large upper critical field, consistent with small Fermi velocities and high T c values of CaKFe 4 As 4 (ξ ∼ v F /(2πk B T c ) [1]).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…This supports the extremely large critical current densities, reported previously for CaKFe 4 As 4 in Ref. [14]. The small coherence length of CaKFe 4 As 4 is compatible with the presence of the large upper critical field, consistent with small Fermi velocities and high T c values of CaKFe 4 As 4 (ξ ∼ v F /(2πk B T c ) [1]).…”
supporting
confidence: 90%
“…Previous magnetisation reported µ 0 H c1 = 22(1) mT [14] when H||c at low temperature which, combined with H c2 values reported here, give κ ∼ 99(2) and λ = 183(6) nm. Using ξ = 1.86 nm, we find that the depairing current density is J d ∼ 1.62 × 10 8 A/cm 2 , which is among the largest of any known iron-based superconductor.…”
Section: Depairing Current Densitysupporting
confidence: 76%
See 1 more Smart Citation
“…Figure 3b shows the H dependence of Jc H//ab derived from the MHLs. Here, we applied a simplified calculation procedure following the previous work 30 Figure 3c shows the MHLs for BaK122 (x = 0.4). In contrast to the case of CaK1144, the MHLs show a peak around self-field, similar to that for H // c. Figure 3d shows the H dependence of Jc H//ab for BaK122.…”
Section: Critical Current Properties In Cakfe4as4mentioning
confidence: 99%
“…In fact, recent studies on vortex pinning properties of CaK1144 reported unusually high Jc 30 as well as vortex dynamics distinct from 122 materials, 31 while the relevant pinning mechanisms remain unsolved. This motivated us to explore the microstructure and the vortex pinning mechanisms in CaK1144.…”
Section: Introductionmentioning
confidence: 99%